2015
DOI: 10.2174/1874210601509010120
|View full text |Cite
|
Sign up to set email alerts
|

Producing Capabilities of Interferon-gamma and Interleukin-10 in Peripheral Blood from Oral Squamous Cell Carcinoma Patients

Abstract: In order to evaluate the Th1 and Th2 responses of Oral Squamous Cell Carcinoma (OSCC) patients, we investigated the cytokine producing capability of peripheral blood (PB), and compared it with clinicopathological appearances of OSCC patients. The production of a Th1-type cytokine, interferon (IFN)-γ, from lipopolysaccharide (LPS)-stimulated PB correlated positively with the frequency of lymph node metastasis. We also investigated the production of a Th2-type cytokine, IL-10, however, no significant correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…DDX60 is a type I interferon-inducible gene in response to viral infections [ 12 ]. Conversely, DDX60 can induce type I IFN (IFN-α/β), which is a well-known potent cytokine under an antiviral innate immune response [ 27 ]. Surprisingly, type I IFN has been implicated in cancer development [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DDX60 is a type I interferon-inducible gene in response to viral infections [ 12 ]. Conversely, DDX60 can induce type I IFN (IFN-α/β), which is a well-known potent cytokine under an antiviral innate immune response [ 27 ]. Surprisingly, type I IFN has been implicated in cancer development [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the activation of inflammatory cytokines [ex. type I interferon (IFN-α/β), tumor necrosis factor-alpha (TNF-α), and type II interferon (IFN)-γ] in response to viral/chemical carcinogens is significantly associated with OSCC [ 27 , 29 , 48 ]. DDX60 could be induced by type I interferon, and the possibility that DDX60 could be induced by other inflammatory cytokines could not be excluded [ 12 , 14 ] and needs further verification.…”
Section: Discussionmentioning
confidence: 99%
“…At present, several cytokines such as IFN-γ, IL-6, GM-CSF, and TGF-β have been reported to be involved in keratinocyte proliferation of the skin, and in the pathogenesis of SCC (2)(3)(4)(5)(6). In this study, we focused on the interaction of cytokines, and showed the expression profile of multiple cytokines in the serum of each patient with SCC.…”
Section: Introductionmentioning
confidence: 95%
“… 1 4 It is known, for example, that cytokines can not only inhibit (interferon (IFN)-γ, tumour necrosis factor (TNF)-α) but also enhance (interleukin (IL)-1β, IL-6, IL-8, transforming growth factor (TGF)-β, monocyte chemoattractant protein-1 (MCP-1), colony-stimulating factor (CSF)-1 and vascular endothelial growth factor (VEGF)) the growth and metastasis of a malignant tumour including breast cancer. 1 , 2 , 5 7 There are correlations between the concentration of certain cytokines in blood (IFN-γ, IL-10 and VEGF) and the degree of tumour vascularisation, tumour cell proliferation, tumour invasiveness and metastasis. 6 , 8 , 9 Nonetheless, there is little data on the extent to which the growth and metastasis of malignant tumours depends on the cytokines produced by immune system cells, how effectively these cytokines enter the tumour through its vascular network and to which degree endogenous (i.e.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 5 7 There are correlations between the concentration of certain cytokines in blood (IFN-γ, IL-10 and VEGF) and the degree of tumour vascularisation, tumour cell proliferation, tumour invasiveness and metastasis. 6 , 8 , 9 Nonetheless, there is little data on the extent to which the growth and metastasis of malignant tumours depends on the cytokines produced by immune system cells, how effectively these cytokines enter the tumour through its vascular network and to which degree endogenous (i.e. intratumoral) cytokine production is not sufficient for tumour growth.…”
Section: Introductionmentioning
confidence: 99%